Modal Realism and Metaphysical Nihilism - Rodriguez-Pereyra, G (2004)
In this paper I argue that Modal Realism, the thesis that there exist non-actual possible individuals and worlds, can be made compatible with Metaphysical Nihilism, the thesis that it is possible that nothing concrete exists. Modal Realism as developed by Lewis rules out the possibility of a world where nothing concrete exists and so conflicts with Metaphysical Nihilism. In the paper I argue that Modal Realism can be modified so as to be compatible with Metaphysical Nihilism. Such a modification makes Modal Realism neither incur further theoretical costs nor lose its theoretical benefits. Thus such a modification constitutes an improvement of Modal Realism.